Nicholas J. Giannestras (1908-1978): a distinguished orthopaedic surgeon, his work, life and times. - Markatos, Konstantinos; Efstathopoulos, Nikolaos; Kaseta, Kiriaki Maria; Nikolaou, Vasileios; Tsoucalas, Gregory; Sgantzos, Markos (Int Orthop, 2015)
The purpose of our study was to summarize all the knowledge concerning the innovative pioneer in the field of orthopaedic surgery, Nicholas J. Giannestras (1908-1978). A thorough study of texts, medical books and reports, in the field of history of medicine, together with a review of the available literature in PubMed, was undertaken. Giannestras left his mark in the history of orthopaedics with his clinical work and his publications, mainly his treatise "Foot Disorders: Medical and Surgical Management" (1973), while his name lingers in Greece with the introduction of spine fusion with the use of metallic implants. He was an eminent university clinical professor of orthopaedics who had harmonically combined academic writing, teaching and clinical research in every field of orthopaedic surgery.